The Influence of Firm Size, Managerial Ownership and Institutional Ownership on Firm Value with Dividend Payout Ratio as Intervening Variable - Arifin, Sugeng Moh; Mildawati, Titik; Suryono, Bambang (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
This study aims to examine and analyze the effect of firm size, managerial ownership and institutional ownership on firm value with the dividend payout ratio (DPR) as the intervening variable. DPR as an intervening variable is expected to be able to show the relationship between firm size, managerial and institutional ownership on firm value. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in the period 2016 to 2018. This study uses purposive sampling method in taking samples of 12 companies. The data in this study were taken from the annual report obtained by direct access to the Indonesia Stock Exchange web address. The analysis method uses path analysis. The results of the analysis show that the variables of firm size, managerial ownership and institutional ownership have an effect on firm value. Meanwhile, the DPR variable is not able to mediate the effect of firm size, managerial ownership and institutional ownership on firm value.